Distinguishing Terrorism Crime from Ordinary Crime- A Comparative Jurisprudential Study - (Journal of Imam Al-Kadhim College, 2024)
In the Name of AllahAll praise is due to Allah, Lord of the worlds, and may peace and blessings be upon Muhammad and his pure progeny. Among the blessings of Allah upon His creation is the blessing of security, which, if lost, causes life to lose one of its most essential elements. In a time where the threats to security have multiplied and their titles have increased, and where danger has become a reality due to terrorist crimes that have spread across the globe, afflicting our society most severely, it has become incumbent upon anyone with means to confront this danger to defend the nation, its sanctities, and personal interests.One of the most important means of confrontation is to reveal and clarify the reality of terrorism, especially after the enemies of Islam and humanity have tried to attribute it to Islam and religious thought. This includes explaining the ways to confront it and the penal legislation that addresses it. Since we live in a country suffering from the effects of this destructive danger while establishing a contemporary state that respects its people's creed and identity, it is necessary to clarify the Islamic Sharia's perspective on the definition of the crime of terrorism and distinguish it from ordinary crimes, comparing it with the stance of secular law.Given the importance of this topic and its impact on people's security, this study investigates the definition of terrorism to enable specialists and readers to distinguish whether a crime is described as terrorism or an ordinary criminal act under the noble Sharia and its equivalent in the prevailing law. The study found that the Imami definition of the crime of banditry aligns with the definitions of secular laws, especially the current Iraqi law on terrorism.The study also explored the conditions, goals, and motives of the perpetrator, which characterize the act as either terrorism or an ordinary crime. The research was structured into a preliminary section discussing the concept of terrorism in language, Islamic jurisprudence terminology, and secular law, and comparing the descriptions of banditry and terrorism. The first chapter examined the characteristics of the crime of terrorism according to Muslim jurists from various schools of thought and in secular law. The second chapter focused on the characteristics of the perpetrator of the crime of terrorism, emphasizing the jurisprudence of the Ahlul Bayt school and Iraqi penal and anti-terrorism laws. The findings of the chapters were reviewed, and recommendations were provided, hoping they would contribute to addressing this dangerous phenomenon.All praise is due to Allah, Lord of the worlds, and may peace and blessings be upon Muhammad and his pure progeny.
Keywords: Concept of Terrorism, People of Daghara, Conditions of the Warrior, Nature of the Crime, Objectives of the Crime of Banditry, Power of the Sword